The Effect Of Waste Management On People’s Knowledge Level (Case Study In The City Of Yogyakarta) - Arsanti, Vidyana; Sekarsih, Fitria Nuraini (LPPM Universitas Tadulako, 2022)
The Total population in the city of Yogyakarta in 2022 is 376 324 people, with a population density of 11 579 people/km2. The population will impact the amount of waste produced, especially household waste. Household-scale waste management is considered the most effective in reducing the waste handled by the Yogyakarta City government. So that it is essential to socialize waste management activities by providing counseling on how to sort organic and inorganic waste, how to make organic waste into compost, and inorganic waste using the Reduce, Reuse, Recycle Disposal (3R + 1 D) method and the Waste Bank program. People in Yogyakarta City curly know how much waste management affects the public knowledge level. The purpose of the study was to determine the effect of waste management on the level of public knowledge. The research method used quantitative descriptive research with the interview and questionnaire. Respondents have participated in the socialization of waste management in Yogyakarta City. The result of the research is that the effect of waste management will increase the knowledge of the people of Yogyakarta City. Public knowledge will also increase community habits and behavior in waste management using the Reduce, Reuse, Recycle, Disposal (3R + 1 D) and the Waste Bank program spread in Yogyakarta City 448 spread on 14 sub-districts.